2013
DOI: 10.1586/14789450.2014.861745
|View full text |Cite
|
Sign up to set email alerts
|

Using proteomics to identify the HBx interactome in hepatitis B virus: how can this inform the clinic?

Abstract: Hepatitis B virus (HBV) is a small and enveloped DNA virus, of which chronic infection is the main risk factor of liver cirrhosis and hepatocellular carcinoma. Hepatitis B virus X protein (HBx) is a multifunctional protein encoded by HBV genome, which have significant effects on HBV replication and pathogenesis. Through directly interacting with cellular proteins, HBx is capable to promote HBV replication, regulate transcription of host genes, disrupt protein degradation, modulate signaling pathway, manipulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 144 publications
(112 reference statements)
0
16
0
Order By: Relevance
“…Recent data has demonstrated that the transdifferentiation of quiescent HSCs into myofibroblasts activates glycolysis and results in lactate accumulation through the induction of HIF1-α for metabolic reprogramming of HSCs [40]. One of the main contributors in HBV infection is HBx protein that has been shown to interact with various host proteins [41, 42]. HIF-1α which is one of the interaction partners of HBx [43], activates the transcription of PKM [44].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data has demonstrated that the transdifferentiation of quiescent HSCs into myofibroblasts activates glycolysis and results in lactate accumulation through the induction of HIF1-α for metabolic reprogramming of HSCs [40]. One of the main contributors in HBV infection is HBx protein that has been shown to interact with various host proteins [41, 42]. HIF-1α which is one of the interaction partners of HBx [43], activates the transcription of PKM [44].…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of transactivation activity by HBx relies on the interactions with several components of the basal transcriptional machinery, cellular sequence-specific transcription factors, or activation of signal transduction pathways. [9] However, the underlying molecular mechanism of HBx activating HBV replication are not fully understood. The "key" host proteins involved in HBx activating HBV transcription and replication are not fully understood.…”
Section: Clinical Relevancementioning
confidence: 99%
“…The trans‐acting transcriptional activity of HBx in enhancing HBV replication may depend on protein–protein interactions. The regulation of transactivation activity by HBx relies on the interactions with several components of the basal transcriptional machinery, cellular sequence‐specific transcription factors, or activation of signal transduction pathways . However, the underlying molecular mechanism of HBx activating HBV replication are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…HBx, encoded by the smallest ORF, is a non-structural viral protein consisting of 154 amino acids with a molecular weight of 17 kDa (1). Previous studies have indicated that HBx is a regulatory protein that benefits viral replication via interaction with numerous cellular proteins (2,3). Furthermore, HBx has an important role in HBV-mediated HCC progression by interacting with transcription factors, activating cellular signaling pathways or inducing aberrant epigenetic changes in order to alter cellular gene expression patterns and to contribute to hepatocarcinogenesis through various underlying mechanisms (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%